Pharmacokinetics, Immunogenicity, and Efficacy of Etanercept in Pediatric Patients With Moderate to Severe Plaque Psoriasis. (6th November 2017) - Langley, Richard G.; Kasichayanula, Sree; Trivedi, Mona; Aras, Girish A.; Kaliyaperumal, Arunan; Yuraszeck, Theresa; Gibbs, John; Gibbs, Megan; Kricorian, Greg; Paller, Amy S.
Abstract: Etanercept has been recently approved in the United States for the treatment of moderate to severe plaque psoriasis in patients aged 4–17 years. The objective of this study was to characterize etanercept pharmacokinetics, immunogenicity, and efficacy in pediatric patients. Data from a phase 3 study and open‐label extension study were analyzed. Etanercept serum concentrations in pediatric patients receiving etanercept 0.8 mg/kg (maximum, 50 mg) weekly were compared with adult psoriasis patients and pediatric patients with juvenile idiopathic arthritis (JIA) who received etanercept 0.4 mg/kg twice weekly. The developments of antietanercept antibodies and efficacy based on the Psoriasis Area and Severity Index were evaluated. Steady‐state trough etanercept concentrations were similar across visits from weeks 12–48, between patients aged 4–11 and 12–17 years, between pediatric and adult psoriasis patients, and between pediatric patients with psoriasis or JIA. Etanercept serum concentrations and safety profiles were similar in patients with (15.9%) and without antietanercept antibodies. Dosing used in the study provided similar exposures and efficacy across ranges of weight and body mass index. Pharmacokinetic, immunogenicity, and efficacy data support 0.8 mg/kg (maximum, 50 mg) weekly dosing of etanercept in patients aged 4–17 years.